Does Bone Resorption Stimulate Periosteal Expansion? A Cross‐Sectional Analysis of β‐C‐telopeptides of Type I Collagen (CTX), Genetic Markers of the RANKL Pathway, and Periosteal Circumference as Measured by pQCT. (April 2014) - Kemp, John P; Sayers, Adrian; Paternoster, Lavinia; Evans, David M; Deere, Kevin; St Pourcain, Beate; Timpson, Nicholas J; Ring, Susan M; Lorentzon, Mattias; Lehtimäki, Terho; Eriksson, Joel; Kähönen, Mika; et al.
ABSTRACT We hypothesized that bone resorption acts to increase bone strength through stimulation of periosteal expansion. Hence, we examined whether bone resorption, as reflected by serum β‐C‐telopeptides of type I collagen (CTX), is positively associated with periosteal circumference (PC), in contrast to inverse associations with parameters related to bone remodeling such as cortical bone mineral density (BMDC). CTX and mid‐tibial peripheral quantitative computed tomography (pQCT) scans were available in 1130 adolescents (mean age 15.5 years) from the Avon Longitudinal Study of Parents and Children (ALSPAC). Analyses were adjusted for age, gender, time of sampling, tanner stage, lean mass, fat mass, and height. CTX was positively related to PC (β = 0.19 [0.13, 0.24]) (coefficient = SD change per SD increase in CTX, 95% confidence interval)] but inversely associated with BMDC (β = –0.46 [–0.52, –0.40]) and cortical thickness [β = –0.11 (–0.18, –0.03)]. CTX was positively related to bone strength as reflected by the strength‐strain index (SSI) (β = 0.09 [0.03, 0.14]). To examine the causal nature of this relationship, we then analyzed whether single‐nucleotide polymorphisms (SNPs) within key osteoclast regulatory genes, known to reduce areal/cortical BMD, conversely increase PC. Fifteen such genetic variants within or proximal to genes encoding receptor activator of NF‐κB (RANK), RANK ligand (RANKL), and osteoprotegerin (OPG) were identified by literature search. Six of the 15 alleles that were inversely related to BMD were positively related to CTX (p < 0.05 cut‐off) (n = 2379). Subsequently, we performed a meta‐analysis of associations between these SNPs and PC in ALSPAC (n = 3382), Gothenburg Osteoporosis and Obesity Determinants (GOOD) (n = 938), and the Young Finns Study (YFS) (n = 1558). Five of the 15 alleles that were inversely related to BMD were positively related to PC (p < 0.05 cut‐off). We conclude that despite having lower BMD, individuals with a genetic predisposition to higher bone resorption have greater bone size, suggesting that higher bone resorption is permissive for greater periosteal expansion. © 2014 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.